Lambda production in e+e- annihilations at 29 GeV: Comparison with Lund-model predictions. - Baringer, P; Abachi, S; Akerlof, C; Beltrami, I; Blockus, D; Bonvicini, G; Brabson, B; Brom, J; Bylsma, BG; Chapman, J; Cork, B; DeBonte, R; et al. (1986)
This paper presents measurements of the inclusive production cross sections of baryons in e+e- annihilations at s=29 GeV. The data sample corresponds to an integrated luminosity of 256 pb-1 collected with the High-Resolution Spectrometer at the SLAC storage ring PEP. Comparisons are made to the predictions of the Lund model. The data are well described with use of a strange-diquark suppression parameter, (usud)(sd), of 0.89 0.10-0.16+0.56, and the measured c+X branching ratio of (23 10)%. © 1986 The American Physical Society.